2013
DOI: 10.1111/febs.12197
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant production of proteoglycans and their bioactive domains

Abstract: Proteoglycans are ubiquitous dynamic molecules that are made up of a protein core to which specific linear glycosylation structures, known as glycosaminoglycans, have been covalently coupled. They have roles in many biological and pathological processes, which have been shown to be dependent on events involving the protein component and/or the glycosaminoglycan chains. This review focuses on the literature describing the recombinant expression and production of proteoglycans known to be present in the extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 202 publications
(264 reference statements)
0
44
0
Order By: Relevance
“…[47] A number of recombinant PGs have been successfully produced. [46,142] Reproducing GAG fine structures attached to recombinant core proteins to recapitulate native GAG structure is a challenging exercise. Production of recombinant, large PGs such as aggrecan and perlecan have their own technical difficulties associated with their massive molecular dimensions and glycosylation characteristics.…”
Section: Recombinant Proteoglycansmentioning
confidence: 99%
“…[47] A number of recombinant PGs have been successfully produced. [46,142] Reproducing GAG fine structures attached to recombinant core proteins to recapitulate native GAG structure is a challenging exercise. Production of recombinant, large PGs such as aggrecan and perlecan have their own technical difficulties associated with their massive molecular dimensions and glycosylation characteristics.…”
Section: Recombinant Proteoglycansmentioning
confidence: 99%
“…[6] Recombinant forms of perlecan domain V have been expressed using human, mouse and drosophila (domain V homologue unc-52) sequences in bacterial and mammalian expression systems. [6] Human domain V sequence encompassing Glu3687 to Ser4391 expressed in HEK-293 cells produced a GAG-free protein core form of domain V, which was named endorepellin (Figure 1). Interestingly, when either mouse domain V sequence, [7][8][9] or human domain V sequence encompassing 37 amino acids into the C-terminal region of domain IV (Leu3626 to Ser4391) named recombinant domain V (rDV) [10] was expressed in HEK-293 cells it resulted in a proteoglycan form of domain V, decorated either with heparan sulfate (HS) or chondroitin sulfate (CS) GAG chains ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharide moieties of proteoglycans constitute complex molecules that may be capable of storing functional information for the cell. A number of investigations have shown that carbohydrate chains of proteoglycans are chemically heterogeneous and structurally irregular, and that the informational content of proteoglycans provides a chemical basis for their intricate and highly specific functions in cellular physiology (Gagneux and Varki 1999;Lord and Whitelock 2013;Paulson 1989). Other studies have shown that these same compounds can play important roles in the interactions of microbes and important human diseases (Tiwari et al 2012).…”
Section: Introductionmentioning
confidence: 99%